Effectiveness of a modified TGfU program in enhancing volleyball skills among elementary school students - Ariwibowo, Yuyun; Sugiyanto, Sugiyanto; Kristiyanto, Agus; Riyadi, Slamet (LPMPP Universitas Negeri Yogyakarta, 2024)
This research is aimed at determining the effectiveness of the modified TGfU volleyball learning model in enhancing the technical skills of male senior students at elementary schools. The research method used to test effectiveness was an experimental research method by comparing the modified TGfU volleyball learning model with traditional physical education classes typically taught by teachers at school. This research was conducted at Kepuh Elementary School with the subjects of 20 male senior students as the experimental group and Patalan Baru Elementary School using the same 20 male senior students as the control group. The instruments used were the American Alliance for Health, Physical Education, and Recreation (AAHPER) Serving Accuracy Test and the Brumbach forearm pass wall-volley test. The application of the modified TGfU volleyball learning model shows the differences in results between the experimental group and the control. The results of the research show that here were differences between the experimental and control groups in the forearm serve (p < 0.001), overhead serve (p < 0.001), and forearm passing skills (p = 0.004), with a p-value of less than 0.05 indicating that the difference is statistically significant. The findings demonstrate that the modified TGfU volleyball learning model outperforms the traditional PE teaching method in enhancing the forearm serve, overhead serve, and forearm passing skills.